Demokrasi Hibrid: Pemikiran Yasraf Amir Piliang tentang Demokrasi Indonesia di Era Digital - Indianto S., Dimas; Nurasih, Wiji; Witro, Doli (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Although it has been implemented for more than two decades since Reformasi 1998, democracy in Indonesia has not been fully established in terms of its principles, ethics, philosphy and orientation. There has been a variety of interpretation and narration of democracy in Indonesia in line of its various actors and supporters. The coming of digital era is making the Indonesian democracy more challenging. Therefore, there is a need for a new concept of democracy that can accommodate all forces of modernity and the specific nature of Indonesia. This article explains a form of democracy offered by Yasraf Amir Piliang as a model of Indonesian demoracy in digital era. Indonesia should apply a form of democracy that maintains national identity while keeps up with modernity in its attempt to realise people sovereignty. This article concludes that hybrid democracy in the forms of liberative, agonistic, autonomous and counter democracies is an appropriate model to implement in Indonesia in the digital era.